2014
DOI: 10.7860/jcdr/2014/10445.5147
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Methods Used to Detect Biofilm Production of Candida Species

Abstract: Candida species were isolated on Sabouraud's dextrose agar. Speciation of Candida was done by Dalmau plate technique on corn meal agar. Also, sugar assimilation and fermentation tests were performed by using 2% concentration of glucose, maltose, sucrose, lactose, galactose, and trehalose were used for test in which Bromothymol blue indicator was used [5]. Microbiology SectionComparison of Various Methods Used to Detect Biofilm Production of Candida Species ABSTRACT Purpose: The biofilm of organisms can be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…In the present study 100% of Candida isolates were found to be biofilm producers by XTT reduction assay. In a study by Dhale et al 16.94% isolates were detected as biofilm positive strains by XTT reduction assay [18], which is in contrast with the present study, but their findings with other methods were also low. Whereas in the present study all isolates were biofilm producers as detected by two different methods.…”
Section: Xtt Reduction Assaycontrasting
confidence: 93%
“…In the present study 100% of Candida isolates were found to be biofilm producers by XTT reduction assay. In a study by Dhale et al 16.94% isolates were detected as biofilm positive strains by XTT reduction assay [18], which is in contrast with the present study, but their findings with other methods were also low. Whereas in the present study all isolates were biofilm producers as detected by two different methods.…”
Section: Xtt Reduction Assaycontrasting
confidence: 93%
“…Biofilm formation on the surface of microplates and the antibiofilm effect of APDT were evaluated using a quantitative crystal violet assay as described previously (7). Briefly, the culture broth media in the wells of the microplates was aspirated gently, and wells were washed twice with distilled water.…”
Section: Photodynamic Treatment Of Biofilms and Antibiofilm Assaymentioning
confidence: 99%
“…40 Briefly, overnight culture was adjusted to 100 lL 0.5 McF units (5 3 10 6 cells/mL) by using SDM (pH 5.6) and then transferred to one of the wells of the 96-well tissue culture plate (ThermoFisher Scientific, Nonclon) already containing 100 lL SDM (pH 5.6). The plate was incubated at 308C for 48 hours.…”
Section: Biofilm-forming Potential Of Ocular Isolates Of C Albicans mentioning
confidence: 99%